Multicenter Double-Blind Placebo-Controlled Study of Gadopentetate Dimeglumine as an MR Contrast Agent: Evaluation in Patients with Cerebral Lesions - Russell, Eric J.; Schaible, Thomas F.; Dillon, William; Drayer, Burton; LiPuma, Joseph; Mancuso, Anthony; Maravilla, Kenneth; Goldstein, Harold A. (American Journal of Neuroradiology, 1989)
A multicenter double-blind randomized study was designed to evaluate and compare the safety and diagnostic efficacy of gadopentetate dimeglumine (Gd-DTPA) (0.1 mmol/kg) against a saline placebo for use as an IV contrast agent for MR. The randomization code provided for a 2:1 ratio of Gd-DTPA and saline patients. Six investigators studied 88 patients with signs and symptoms of a cerebral lesion. Although safety data were complete in all 88 cases, only 83 had valid efficacy data (57 received Gd-DTPA, 26 placebo). Three patients were excluded from efficacy evaluation because of incomplete scans or scans with severe motion artifacts. Two patients were excluded for protocol variations (did not have a mass lesion). The protocol required that spin-echo MR images be acquired both before and after infusion at mode 1, 500/30/2 (TR/TE/excitations), and at a single-echo mode 2 sequence within a selected range, 1500-2000/56-90/2. Additional TEs could also be used at the discretion of each investigator. Efficacy was determined by comparing post- with preinjection images for relative degree of enhancement and improvement of diagnostic ability after injection, and by comparing these results with placebo results. Enhancement was reported in 43 (75%) of 57 Gd-DTPA patients and in none of the 26 placebo patients. Improvement of diagnostic ability was noted in 37 of 57 Gd-DTPA patients and in no placebo patients. Of 17 patients receiving Gd-DTPA for whom no diagnosis could be made before infusion, nine of 17 were diagnosed after infusion. By comparison, none of five patients not diagnosed before infusion of placebo could be diagnosed after infusion. Of 43 patients in whom lesion enhancement was observed after Gd-DTPA infusion, the diagnosis changed after infusion in 16 (37%) and the number of lesions detected after infusion increased in 10 (23%). Safety studies showed no clinically significant abnormal trends. Minor changes in blood pressure, pulse, and serum iron levels were noted in a higher percentage of Gd-DTPA patients. This study confirms that Gd-DTPA is an efficacious contrast agent for use with MR and that it exhibits excellent patient tolerance. Enhancement allows for a decisive diagnosis to be made in selected cases in which such capability had previously been lacking with unenhanced MR.